Curcumin Attenuates Beta-Amyloid-Induced Neuroinflammation via Activation of Peroxisome Proliferator-Activated Receptor-Gamma Function in a Rat Model of Alzheimer's Disease - Liu, Zun-Jing; Li, Zhong-Hao; Liu, Lei; Tang, Wen-Xiong; Wang, Yu; Dong, Ming-Rui; Xiao, Cheng (Frontiers in Pharmacology, 2016)
Neuroinflammation is known to have a pivotal role in the pathogenesis of Alzheimer’s disease (AD), and curcumin has been reported to have therapeutical effects on AD because of its anti-inflammatory effects. Curcumin is not only a potent PPARγ agonist, but also has neuroprotective effects on cerebral ischemic injury. However, whether PPARγ activated by curcumin is responsible for the anti-neuroinflammation and neuroprotection on AD remains unclear, and needs to be further investigated. Here, using both APP/PS1 transgenic mice and beta-amyloid-induced neuroinflammation in mixed neuronal/glial cultures, we showed that curcumin significantly alleviated spatial memory deficits in APP/PS1 mice and promoted cholinergic neuronal function in vivo and in vitro. Curcumin also reduced the activation of microglia and astrocytes, as well as cytokine production and inhibited nuclear factor kappa B (NF-κB) signaling pathway, suggesting the beneficial effects of curcumin on AD are attributable to the suppression of neuroinflammation. Attenuation of these beneficial effects occurred when co-administrated with PPARγ antagonist GW9662 or silence of PPARγ gene expression, indicating that PPARγ might be involved in anti-inflammatory effects. Circular dichroism and co-immunoprecipitation analysis showed that curcumin directly bound to PPARγ and increased the transcriptional activity and protein levels of PPARγ. Taking together, these data suggested that PPARγ might be a potential target of curcumin, acting to alleviate neuroinflammation and improve neuronal function in AD.